MUZAKKI LOYALTY: SYSTEMATIC LITERATUR REVIEW - Alda; Aziz, Saipul (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
This study aims to investigate the trend of Muzakki Loyalty in order to identify what research is needed in the future. In addition, it also explores the relationship model between how the current publication trend of Muzakki Loyalty and how the results of a systematic literature review direct future research. The design/methodology/approach in this study uses a systematic literature review and Meta-Analyses (PRISMA) analysis by reviewing articles published from 2014 to 2023. The PRISMA procedure involves several stages, including identification, screening, eligibility, analysis and conclusions based on the findings. The results of the study found that the trend with the keyword Muzakki Loyalty was not widely used or appeared in the article. With the more dominant keyword appearing, namely Zakat, which was used 15 times from 2016-2023. Furthermore, with the keyword Muzakky which was used 11 times from 2016-2023. And Muzakki Loyalty only appeared 1 time from articles starting from 2016-2023. Therefore, it can be concluded that the results of the study with the keyword muzakki loyalty are rarely used in articles. For this reason, further research can be done by adding OR, AND to add keywords so that the research can be broader..